2022
DOI: 10.3892/ol.2022.13396
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑126 expression in the peripheral white blood cells of patients with breast and ovarian cancer is a potential biomarker for the early prediction of cancer risk in the carriers of methylated BRCA1

Abstract: Constitutive breast cancer type 1 gene (BRCA1) promoter methylation is associated with increased cancer risk, but its role in cancer-free (CF) female carriers is incompletely understood. MicroRNA (miR) is modulated during early tumorigenesis. The present study assessed the modulation of miR-126 expression in the peripheral white blood cells (WBC) of patients with breast cancer (BC) and ovarian cancer (OC) as a biomarker of cancer risk in BRCA1 methylation carriers. A total of 1,114 female subjects [502 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…Moreover, studying the molecular effects of BRCA1 epimutation in WBCs has shown that there are cancer-related molecular changes that can occur in adult carriers and, more importantly, in newborn carriers. These changes are similar to those seen in females who have been diagnosed with breast cancer and ovarian cancer [5,9,25]. Thirdly, in a recent study [5], we found that the WBCs of CF BRCA1 methylation carriers had less ILR2G (a T cell functional molecule), suggesting that these carriers have reduced antitumor immunity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, studying the molecular effects of BRCA1 epimutation in WBCs has shown that there are cancer-related molecular changes that can occur in adult carriers and, more importantly, in newborn carriers. These changes are similar to those seen in females who have been diagnosed with breast cancer and ovarian cancer [5,9,25]. Thirdly, in a recent study [5], we found that the WBCs of CF BRCA1 methylation carriers had less ILR2G (a T cell functional molecule), suggesting that these carriers have reduced antitumor immunity.…”
Section: Discussionsupporting
confidence: 86%
“…Based on our data, almost 19% of CF Saudi women are carriers of constitutional epimutations: 10% carry MGMT epimutations and 8.6% carry BRCA1 epimutations from early on in life. Mounting evidence substantiates the notion that such persons are at a heightened risk of developing breast and/or ovarian cancer [ 4 , 5 , 9 , 25 , 31 , 32 , 33 ]. We previously demonstrated that the levels and arrangements of CpG island methylation at the BRCA1 promoters in WBCs are comparable among cancer patients, newborns, and adult BRCA1 methylation carriers [ 4 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To evaluate the use of WBC miR-155-5p as a molecular biomarker for the assessment of cancer risk in CF-BRCA1 methylation-carrying females, we measured the level of WBC miR-155-5p in ten BRCA1-methylation carriers, as used in our previous study [39]. Notably, similar to the BRCA1-methylation-positive patients with breast and ovarian cancers, miR-155-5p was significantly higher in the BRCA1-methylated carriers compared to age-matched controls (p = 0.0418) (Figure 6A).…”
Section: Mir-155-5p Is Elevated In Wbcs Of Brca1-methylation Female C...mentioning
confidence: 99%
“…Few reports on miRNAs and the regulation of candidate genes involving the risk of BC are still inadequate in the Saudi population [ 14 , 15 ]. In addition, research on candidate gene miRNA polymorphisms, miR-196a2 (MIM 609687), miR-146a (MIM 610566), and miR-499 (MIM 613614), and their implications on BC risk is still insufficient.…”
Section: Introductionmentioning
confidence: 99%